Potential Direct Regulators of the Drosophila yellow Gene Identified by Yeast One-Hybrid and RNAi Screens. Issue 10 (1st October 2016) - Kalay, Gizem; Lusk, Richard; Dome, Mackenzie; Hens, Korneel; Deplancke, Bart; Wittkopp, Patricia J
Abstract: The regulation of gene expression controls development, and changes in this regulation often contribute to phenotypic evolution. Drosophila pigmentation is a model system for studying evolutionary changes in gene regulation, with differences in expression of pigmentation genes such as yellow that correlate with divergent pigment patterns among species shown to be caused by changes in cis - and trans -regulation. Currently, much more is known about the cis -regulatory component of divergent yellow expression than the trans -regulatory component, in part because very few trans -acting regulators of yellow expression have been identified. This study aims to improve our understanding of the trans -acting control of yellow expression by combining yeast-one-hybrid and RNAi screens for transcription factors binding to yellow cis -regulatory sequences and affecting abdominal pigmentation in adults, respectively. Of the 670 transcription factors included in the yeast-one-hybrid screen, 45 showed evidence of binding to one or more sequence fragments tested from the 5′ intergenic and intronic yellow sequences from D. melanogaster, D. pseudoobscura, and D. willistoni, suggesting that they might be direct regulators of yellow expression. Of the 670 transcription factors included in the yeast-one-hybrid screen, plus another TF previously shown to be genetically upstream of yellow, 125 were also tested using RNAi, and 32 showed altered abdominal pigmentation. Nine transcription factors were identified in both screens, including four nuclear receptors related to ecdysone signaling ( Hr78, Hr38, Hr46, and Eip78C ). This finding suggests that yellow expression might be directly controlled by nuclear receptors influenced by ecdysone during early pupal development when adult pigmentation is forming.